Facilitation of professional education: definiton, concept, practice - Струпинська, Н. В.; Kuznets, Simon (НТУ "ХПІ", 2015)
Definitions of the term ―facilitation‖ and its advantages / disadvantages have been analyzed in the article. Main styles of the facilitation of professional education have been described. Guiding principles for assisting professional education practitioners facilitate learner-centered education have been mentioned. Six dimensions of facilitation have been presented. Steps of preparation to the effective facilitation and steps how you might generate a good working dynamic with your students have been developed. Conflict indicators and conflict resolution tactics have been described with the requirements to the effective facilitation of professional education.

У статті проаналізовано визначення терміна «фасилітація», її пе- реваги та недоліки. Описано основні стилі фасилітації професійної освіти. Представлено основні принципи для тих, які практикуються у фасилітації професійної освіти. Описано шість ведучих аспектів фасилітації. Розроб- лено послідовність кроків щодо підготовки до ефективної фасилітації та створення позитивної динаміки роботи студентів. Описано індикатори конфлікту в аудиторії і тактика вирішення цих конфліктів; крім того, на- ведено вимоги для ефективної фасилітації професійної освіти.
Сприяння науки: DÉFINI-тон, концепція, практика
Keywords: facilitation; effective facilitation; professional education; style of facilitation; student; lecturer; ефективна фасилітація; професійна освіта; стиль фасилітації; студент; викладач